2021
DOI: 10.1021/acs.jcim.1c00589
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoprint: A Combination of a Pharmacophore Fingerprint and Artificial Intelligence as a Tool for Computer-Aided Drug Design

Abstract: Structural fingerprints and pharmacophore modeling are methodologies that have been used for at least 2 decades in various fields of cheminformatics, from similarity searching to machine learning (ML). Advances in in silico techniques consequently led to combining both these methodologies into a new approach known as the pharmacophore fingerprint. Herein, we propose a high-resolution, pharmacophore fingerprint called Pharmacoprint that encodes the presence, types, and relationships between pharmacophore featur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…These results indicate that molecular fingerprints based on substructure and pharmacophores can better represent the toxic fingerprints for DILI prediction. Meanwhile, pharmacophore-based fingerprints named Pharmcoprint show that pharmacophore fingerprints are superior to other molecular fingerprints for protein targets prediction [ 70 ]. In the pre-experiment, we also found that the fingerprint based on pharmacophores had the highest accuracy in the single fingerprint experiment, but the prediction accuracy was higher when it was combined with other fingerprints by using R-E-GA.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that molecular fingerprints based on substructure and pharmacophores can better represent the toxic fingerprints for DILI prediction. Meanwhile, pharmacophore-based fingerprints named Pharmcoprint show that pharmacophore fingerprints are superior to other molecular fingerprints for protein targets prediction [ 70 ]. In the pre-experiment, we also found that the fingerprint based on pharmacophores had the highest accuracy in the single fingerprint experiment, but the prediction accuracy was higher when it was combined with other fingerprints by using R-E-GA.…”
Section: Resultsmentioning
confidence: 99%
“… 23 A 2D pharmacophore fingerprint is a form of a binary code that contains pharmacophore properties. 24 27 These pharmacophore fingerprints containing molecular fragments have been applied with multiple artificial intelligence-related models such as PTML, 28 , 29 Pharmacoprint, 27 and Pharm-IF. 30 …”
Section: Introductionmentioning
confidence: 99%
“…In the benchmark classification tasks, the authors dropped the compounds between active and inactive to define a distinct boundary: for the DAT and hERG data sets, the compounds with pK i or pIC 50 values between 5 and 6 were excluded; 65 for the D 2 R data set, the compounds with pK i or pIC 50 values between 6 and 7 were removed. 66 Therefore, to fairly compare our results to theirs, we also followed the same preprocessing strategies so that the data sets can be directly compared.…”
mentioning
confidence: 99%
“…This work studied 36 data sets for 32 different protein targets. The data were collected from refs and and the ChEMBL database . These data sets are summarized in Table S1.…”
mentioning
confidence: 99%
See 1 more Smart Citation